HUBUNGAN INDEKS MASSA TUBUH DENGAN KEBUGARAN KARDIOVASKULAR PADA SISWI SMP NEGERI 38 PEKANBARU - Nur, Rezki Muhammad; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Problem in this research is, many student of obese people who lazy to exercise, not even rarely they do not want to exercise for various reasons. In addition, many students are slow in moving and quickly experience fatigue or poor physical fitness. Based on these problems the researchers conducted a research study about the relationship of obesity with physical fitness levels in children by using the body mass index test with Foster test. The form of this research is correlation research, with population students of SMP Negeri 38 Pekanbaru, data in this research is 25% from total population which is 32 people. The instrument performed in this study is a Body Mass Index test, which aims to measure a person's body mass index and Foster Test test, this test to determine how the heart condition after doing light exercise. After that, the data were processed by statistics, to test the normality by lilifors test at a significant level of Î± (0.05). The hypothesis proposed is a relationship of Body Mass Index with cardiovascular fitness. Based on statistical data analysis, there is an average IMT of 19.77 and an average Foster test of 12.44, rhitung = 0.8228. At a significant level of 5% was found rtabel = 0.3494. thus rhitung> rtabel or 0,8228> 0,3494. This shows the correlation between variable X and variable Y or there is a significant relationship of body mass index with cardiovascular fitness at SMPN 38 Pekanbaru. Keywords: Body Mass Index, Cardiovascular Fitness